Respuesta :
The resulting function is (f-g)(x) = 5 · x⁴ + 3 · x² + 10.
The resulting function is (f • g) (x) = 3 · (3 · x⁵ - 5 · x⁴ + 3 · x² - 15)⁵ + 6 · (3 · x⁵ - 5 · x⁴ + 3 · x² -15)² - 5.
How to apply subtraction between two functions
Let be [tex]f(x)[/tex] and [tex]g(x)[/tex] polynomial functions, the subtraction between between the two functions implies the subtraction of similar terms. If we know that [tex]f(x) = 3\cdot x^{5}+6\cdot x^{2}-5[/tex] and [tex]g(x) = 3\cdot x^{5}-5\cdot x^{4}+3\cdot x^{2}-15[/tex], then the subtraction between the two functions:
[tex](f-g)(x) = (3\cdot x^{5}+6\cdot x^{2}-5)-(3\cdot x^{5}-5\cdot x^{4}+3\cdot x^{2}-15)[/tex]
[tex](f-g)(x) = 5\cdot x^{4}+3\cdot x^{2}+10[/tex]
The resulting function is (f-g)(x) = 5 · x⁴ + 3 · x² + 10. [tex]\blacksquare[/tex]
How to apply composition between two functions
The composition between two functions, the independent variable of the former function by the latter function. If we know that [tex]f(x) = 3\cdot x^{5}+6\cdot x^{2}-5[/tex] and [tex]g(x) = 3\cdot x^{5}-5\cdot x^{4}+3\cdot x^{2}-15[/tex], then the composition between the two functions:
[tex]f\,\circ\,g\,(x) = 3\cdot (3\cdot x^{5}-5\cdot x^{4}+3\cdot x^{2}-15)^{5}+6\cdot (3\cdot x^{5}-5\cdot x^{4}+3\cdot x^{2}-15)^{2}-5[/tex]
(f • g) (x) = 3 · (3 · x⁵ - 5 · x⁴ + 3 · x² - 15)⁵ + 6 · (3 · x⁵ - 5 · x⁴ + 3 · x² -15)² - 5. [tex]\blacksquare[/tex]
To learn more on functions, we kindly invite to check this verified question: https://brainly.com/question/5245372